PT and PTT; Are They Significant Indicators of Poor Prognosis in Severe Renal Failure Patients? - Alshammary, Amal F.; Alsowyan, Mohamed; Alawain, Abdullah; Alghamdi, Suad; Alsiary, Rawiah; Alsofyani, Abeer; Almatrrouk, Shaihana; Alonazi, Fahad N.; Alanazi, Mona; Aldahish, Afaf; et al. (International Journal of Innovative Research in Medical Science, 2024)
The coagulation system has gained significant interest in the recent past, especially in patients diagnosed with renal failure, as they are susceptible to significant comorbidity that requires anticoagulation. Research indicates that patients diagnosed with renal failure are at an increased risk of developing complications associated with coagulation abnormalities. Renal failure patients experience excessive bleeding even on new anticoagulants due to pharmacokinetic profile changes of the compounds. However, even without anticoagulants, the coagulation systems in patients with renal failure are profoundly changed, leading to significant morbidity and mortality in such patients. The underlying reasons for such problems involve the changes in the interaction of coagulation system components such as the platelets, coagulation cascade, and the vessel wall in the metabolic conditions of renal pathology. One meaningful way of evaluating the coagulation status of patients diagnosed with renal failure is through prothrombin time (PT) and partial thromboplastin time (PTT) blood tests. The two laboratory tests are used to evaluate coagulation disorders where the PT test measures the time it takes for blood to clot in response to prothrombin, a clotting factor, activation, and the PTT test measures the time it takes for blood to clot in response to clotting factor activation. This study evaluated PT and PTT levels of renal failure patients to determine their relationship with the disease’s severity and prognosis. The study was conducted as a collaboration study between PSAU and KELANA Association. Data were collected from 20 samples, and statistical analysis was done using the SPSS software version 2.0. The research findings indicated insignificant statistical differences between PT levels of renal failure patients and controls, while PTT levels in males significantly differed between patients and the controls. The study indicates that PTT levels can be used to indicate coagulation abnormalities in male patients diagnosed with renal failure.